النسل بين التنظيم والتحديد فى الإسلام - حسن، الهادي أحمد محمد (جامعة الزعيم الأزهري, 2014)
يتبين من هذا العرض أن تحديد النسل لا يجوز أن يأخذ شكل القانون العام الذي يدعى إلى تطبيقه والعمل به والدعاية له سواء في ذلك الدول الكبيرة أو الصغيرة. وأن أصول الإسلام ومبادئه تحرمه وتمقته وأنه دخيل على الإسلام والمسلمين ويكفي قوله تعالى (وَاللَّهُ جَعَلَ لَكُمْ مِنْ أَنْفُسِكُمْ أَزْوَاجًا وَجَعَلَ لَكُمْ مِنْ أَزْوَاجِكُمْ بَنِينَ وَحَفَدَةً وَرَزَقَكُمْ مِنَ الطَّيِّبَاتِ أَفَبِالْبَاطِلِ يُؤْمِنُونَ وَبِنِعْمَةِ اللَّهِ هُمْ يَكْفُرُونَ ) ( ) الله عز وجل وحده هو المسؤول عن تحديد الرزق لعباده، وأن ليس للإنسان أن يقحم نفسه في هذه المهمة فالأمر كله لله. ونحن عباد الله لا نملك من هذا الأمر شيئًا. فالأرض ما ضاقت يومًا ولن تضيق إلى أن يرثها الله ومن عليها، وهو القادر على فتح أبواب الخير وإنزال البركة للعباد. قال الله تعالى: (وَلَوْ أَنَّ أَهْلَ الْقُرَى آَمَنُوا وَاتَّقَوْا لَفَتَحْنَا عَلَيْهِمْ بَرَكَاتٍ مِنَ السَّمَاءِ وَالْأَرْضِ وَلَكِنْ كَذَّبُوا فَأَخَذْنَاهُمْ بِمَا كَانُوا يَكْسِبُونَ )( ) الأولاد نعمة تتعلق بها قلوب البشر، وترجو لتأنس بها من الوحشة وتقوى بها عند الوحدة، وتكون قرة عين لها في الدنيا والآخرة، فهل نسمي الولد الثالث أو الرابع غلطة؟ بينما يرحب غيرنا بأولاد الزنا. إن من ينادون بتحديد النسل وتنظيمه ويروجون لوسائله في بلاد المسلمين يتعاملون مع هذه الوسائل في بلادهم بحذر، لما لها من عواقب وخيمة بات الكل يعرفها، وهؤلاء يخشون الكثرة في بلادنا ليس لأنها تضرنا بل لأنها تضرهم وتزعزع كيانهم. The Concept of Filmily planning in Islam Birth control should not take the form of a general law which all nations , big or small , are asked to carry out as it is shown in this research . It has been applied with much propaganda mainly in Muslim countries! The fundamental faith and principal of Islam detest and ban birth control as it is alien to Muslims . Almighty Allah's words reads: (And God has made for you mates of your own nature ,And made for you ,out of them , sons and daughters and grandchildren , all provided for you , sustenance of the best : with they then believe in rain things , and be ungrateful for God's favour ?)•) Almighty Allah alone is the benefactor who undertook to distribute the wealth and means of living for his slaves ! so humans shouldeen't interfere in this matter because Allah looks after it, and we the slaves of Allah . do not master anything in that . the land had never narrowed and will not decrease in width until Allah inherits the land and who is on it. He alone is able to open the doors of blessings and prosperity for His slaves . Allah says : (If the people of the towns had but believed and fearsd and feared God , We should in dead have opened out to them blessing from Heaven and misdeeds .)( ) The children are favor grace which the hearts of all the humans love and hope to make them a comfort for them in the gloomy days , and support them when they feel the lonelyness . and comfort them in this world and in the day of recreation. should we call the third or the fourth child a mistake while others welcome unfathed children? Those who call for birth control and propagandize for that in Muslim countries awaring of its effect apon us . They fear the increasing of population in Muslim countries which frighten them .because they fear the spread of Islam to shake their thron.
Keywords: تحديد النسل -- تنظيم النسل -- تنظيم الأسرة -- الفقه الإسلامى